2010
DOI: 10.1016/j.neuron.2009.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Are the Dorsal and Ventral Hippocampus Functionally Distinct Structures?

Abstract: One literature treats the hippocampus as a purely cognitive structure involved in memory; another treats it as a regulator of emotion whose dysfunction leads to psychopathology. We review behavioral, anatomical, and gene expression studies that together support a functional segmentation into 3 hippocampal compartments dorsal, intermediate and ventral. The dorsal hippocampus, which corresponds to the posterior hippocampus in primates, performs primarily cognitive functions. The ventral (anterior in primates) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

164
2,386
8
40

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,767 publications
(2,672 citation statements)
references
References 138 publications
164
2,386
8
40
Order By: Relevance
“…In the fear conditioning experiments (Experiment 2 and 3), we aimed to corroborate our previous finding that ventral hippocampal muscimol (1 µg / 0.5 µl / side) disrupts contextual, but not tone, fear conditioning (Bast et al, 2001a) and to extend this finding by demonstrating similar effects of dorsal hippocampal muscimol. Such an outcome would be consistent with the idea that contextual fear conditioning requires dorsal hippocampal mechanisms mediating the formation of context representations, and ventral hippocampal mechanisms relating the context representations to fear processing via subcortical structures, including the amygdala (Maren and Fanselow, 1995;Anagnostaras et al, 2001;Bast et al, 2001a;Bannerman et al, 2004;Fanselow & Dong, 2010). While the ventral hippocampus has also been implicated in tone fear conditioning (Bast et al, 2001b;Bannerman et al, 2004), ventral hippocampal muscimol did not significantly reduce tone fear conditioning in our previous study (even though there was a numerical reduction), and we argued that partial inhibition of neuronal activity in the ventral hippocampus via GABA-A receptor stimulation may not sufficiently interfere with ventral hippocampal processing to affect tone fear conditioning (in contrast, more general ventral hippocampal inactivation by the sodium channel blocker tetrodotoxin markedly impaired tone fear conditioning) (Bast et al, 2001a).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…In the fear conditioning experiments (Experiment 2 and 3), we aimed to corroborate our previous finding that ventral hippocampal muscimol (1 µg / 0.5 µl / side) disrupts contextual, but not tone, fear conditioning (Bast et al, 2001a) and to extend this finding by demonstrating similar effects of dorsal hippocampal muscimol. Such an outcome would be consistent with the idea that contextual fear conditioning requires dorsal hippocampal mechanisms mediating the formation of context representations, and ventral hippocampal mechanisms relating the context representations to fear processing via subcortical structures, including the amygdala (Maren and Fanselow, 1995;Anagnostaras et al, 2001;Bast et al, 2001a;Bannerman et al, 2004;Fanselow & Dong, 2010). While the ventral hippocampus has also been implicated in tone fear conditioning (Bast et al, 2001b;Bannerman et al, 2004), ventral hippocampal muscimol did not significantly reduce tone fear conditioning in our previous study (even though there was a numerical reduction), and we argued that partial inhibition of neuronal activity in the ventral hippocampus via GABA-A receptor stimulation may not sufficiently interfere with ventral hippocampal processing to affect tone fear conditioning (in contrast, more general ventral hippocampal inactivation by the sodium channel blocker tetrodotoxin markedly impaired tone fear conditioning) (Bast et al, 2001a).…”
Section: Introductionsupporting
confidence: 71%
“…Thus, both dorsal and ventral hippocampal muscimol infusions disrupted contextual fear conditioning when the resulting conditioned context fear in the control group was relatively moderate (20-50% freezing) (present study, Experiments 2 and 3, 0.5 µg / 0.5 µl / side; Esclassan et al, 2009, 0.25 µg / 0.25 µl / side), whereas neither dorsal nor ventral hippocampal muscimol infusions affected contextual fear conditioning when conditioning resulted in stronger conditioned freezing (50-70%) (Maren & Holt, 2004, 0.25 µg / 0.25 µl / side;Matus-Amat et al, 2004, 0.5 µg / 0.5 µl / side;Biedenkapp and Rudy, 2008, 0.5 µg / 1 µl / side) (with the exception of Wang et al (2012), who reported anterograde context fear deficits following dorsal hippocampal muscimol (0.5 µg / 0.5 µl / side) with context freezing levels of nearly 60%). That dorsal and ventral hippocampal muscimol infusions cause anterograde deficits in contextual fear conditioning, depending on the strength of the conditioing is consistent with the following view: i) contextual fear conditioning normally requires dorsal and ventral hippocampus (with dorsal hippocampus mediating the formation of contextual representations and ventral hippocampus relating these representations to fear processing via subcortical sites, such as the amygdala; Maren and Fanselow, 1995;Anagnostaras et al, 2001;Bast et al, 2001a;Bannerman et al, 2004;Fanselow & Dong, 2010); ii) an alternative extra-hippocampal system can support contextual fear conditioning, but is less efficient than the hippocampus and, thus, is not able to sustain conditioning under more demanding circumstances, such as those that would result in weak contextual fear (Fanselow, 2010). The strength of conditioning may also partly determine whether or not ventral hippocampal muscimol infusions disrupt tone fear conditioning.…”
Section: Ventral and Dorsal Hippocampal Muscimol Impair Contextual Bmentioning
confidence: 59%
See 1 more Smart Citation
“…The analysis of resident microglia and blood‐derived macrophages was performed by quantifying Cx3cr1‐GFP‐positive (Cx3cr1‐GFP+) and Ccr2‐RFP‐positive (Ccr2‐RFP+) cells in the entire dorsal DG region of the hippocampus (the granule cell layer including the subgranular zone) and the entire dorsal CA region of the hippocampus (the pyramidal cell layer from CA1‐3) (Fanselow and Dong, 2010; Qiu et al, 2007). For quantification of immunopositive cells in the DG and the CA regions, ten consecutive 0.5μm z ‐stack images of the sections were acquired using Axio Imager M2 microscope with Apotome attachment (Carl Zeiss) at 20× magnification and compressed in a single image (Kadam et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the role of this tract in cognition, surprisingly little is understood about the organization of the fibers within the human fornix and how this might relate to its various connections. The principal motivation to examine their topography arises from the growing evidence for functional differences along the anterior–posterior axis of the hippocampus (Collin, Milivojevic, & Doeller, 2015; Fanselow & Dong, 2010; Poppenk, Evensmoen, Moscovitch, & Nadel, 2013; Strange, Witter, Lein, & Moser, 2014). For instance, evidence from functional neuroimaging studies suggests a role of the posterior hippocampus in spatial navigation (e.g., Hartley, Maguire, Spiers, & Burgess, 2003), whereas anterior hippocampus has been associated with goal‐directed spatial decision making (Viard, Doeller, Hartley, Bird, & Burgess, 2011).…”
Section: Introductionmentioning
confidence: 99%